Aspectos epidemiológicos e manejo integrado do brusone do trigo - Pizolotto, Carlos Augusto (2019)
The emergence of blast pathogen (Magnaporthe oryzae) infecting wheat (Triticum aestivum L.) is relatively recent in Brazil. The studies published so far have indicated the occurrence of a genetic variability and virulence variability between the M. oryzae populations that are infecting wheat in Brazil. Seedlings and detached heads from 11 wheat cultivars and one barley lineage (T & C) were used in experiments conducted under controlled conditions in which individualized conidial suspension of 89 M. oryzae isolates and two M. grisea isolates were used in inoculation procedures. Presence of the 2NS chromosomal segment in the T & C genotypes was determined via PCR. It was verified that M. oryzae virulence groups are widely distributed in the country and that, due to the high resistance to blast demonstrated, Santa Fe wheat cultivar plays a prominent role as a source of resistance to the disease. In addition, it was found that the evaluation of wheat M. oryzae isolates for virulence generates a very distinct classification patterns depending on whether the object of infection analysis is leaf or head. To monitor the saprotrophic development of M. oryzae on wheat debris and explore the importance of crop residues as a source of inoculum, wheat cultivars BRS 229 and Anahuac 75, moderately and highly susceptible to the disease, respectively, were inoculated with a spore suspension of 10 -5 conidia mL -1 using an aggressive (Py 12.1.209) and a less aggressive (Py 12.1.132) isolate. At maturity, a portion of leaves, stems and spikes were detached from plants, and a group of ten lesions were randomly selected and marked on each type of plant organ. The air -dried plant organs were placed separately inside bags and exposed outside. Each 14 days, samples were taken from the field and tested for sporulation. Sporulation of the fungus was observed on the wheat residues for up to five months. For managing blast disease in wheat, the chemical control is the main option, due to absence of resistance wheat cu ltivars, but it needs to improve wheat head coverage. The experiments were arranged in a randomized block design in a 4x2 factorial scheme, four spray nozzles and two adjuvants, under three replications. The fungicides were sprayed 24 hours before the wheat heads inoculation. In the greenhouse experiment were evaluated the coverage quality by four different spray nozzles in artificial wheat heads surrounded by a hydrosensitive cards, the head blast severity - SEVE and the number of infection points on the rachis – NPI. In the greenhouse experiment, the lowest values to SEVE and NPI were found in the treatment T9 (mancozeb + Break-Thru + Grip: TJ60 10002-60 o ). In field conditions the wheat blast incidence - INC and head blast severity - SEVE were evaluated. The treatment with mancozeb (T9) showed the lowest averages for both disease variables, however, treatment T9 did not differ statistically of treatment T8 for INC variable, for the variable SEVE, treatment T9 not differ statistically of treatments that Break-Thru® adjuvant was added in the spray solution (T5,T6,T7 e T8).